Treatment patterns, outcomes, and resource utilization of patients with metastatic melanoma in the U.K.: the MELODY study. (January 2014) - Lorigan, P.; Marples, M.; Harries, M.; Wagstaff, J.; Dalgleish, A.G.; Osborne, R.; Maraveyas, A.; Nicholson, S.; Davidson, N.; Wang, Q.; Pericleous, L.; Bapat, U.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Historically, patients with advanced melanoma have had a very poor prognosis, with limited treatment options outside of clinical trial participation. What does this study add? MELODY is the first observational study to provide a detailed description of treatment patterns and outcomes among U.K. patients with advanced melanoma treated in routine clinical practice, providing a historical context for assessing outcomes in the modern era of targeted agents and immunotherapies.